ANALISIS PEMROSESAN KOMPRESI CITRA MENGGUNAKAN TRANSFORMASI WAVELET - Agoes, Suhartati (Jurnal Teknik Elektro, 2009)
Generally, an image consists of huge data which requires large capacity media storage. Then, if the image is going to be transmitted through telecommunication media, the transmission channel to be used must have large bandwidth. The increasing capacity and bandwidth of transmission channel cause data sending such as image with large data becomes inefficient. Compression process can be conducted to improve the efficiency in image sending process. Image compression is a process to reduce the bit used in representing an image. The purpose of compression process is to obtain image from reconstruction with smaller bit without reducing the quality of the original image. To handle it, an implementation of suitable image compression is needed and one of them is by using wavelet transformation. Simulation result shows that grey image reconstruction âlenaâ is best for coif2 filter with PSNR score 38.6156, âpeppersâ image is best for coif2 filter with PSNR score 41.8141 and âcoinsâ image is best for coif2 filter with PSNR score 40.6666. While the reconstruction image with âwbarbâ color is best for coif2 filter with PSNR score 37.2284, âearthâ image is best for coif2 filter with PSNR score 37.3550 and âclownâ image is best for coif2 filter with one level decomposition with PSNR score 37.5432.Keywords: Image, Wavelet, Compression, PSNR, Perf0